Skills Availability in the Jordanian Educational Process Outputs Compared with the Local Labor Market Needs - Osamh M. Obidat; Saidh Sadh (University of Science and Technology, Yemen, 2010)
Skills Availability in the Jordanian Educational Process Outputs Compared with the Local Labor Market Needs Abstract The aim of this study is to measure the level of soft skills obtaining among Jordanian public and private university undergraduates. This paper focused on studying four skills; Communication, Technology Skills, Initiative and Creativity, and Foreign Languages skills. Two hundreds and twenty eight students (120 males and 108 females) from public and private Jordanian universities in the academic year 2007/2008 participated in this study. Data for this study was collected through answering developed questionnaire.     The results of the study showed that both public and private university undergraduate students in Jordan acquire soft skills to a large extent. The study also showed that there were some variation in the level of skills acquired based on gender, type of major, as well as university. This comes because of the attempt of the Jordanian higher education policy makers to improve the quality of the higher education sector and make it more responsive to the economy. The study ended up with some recommendation and suggestions